STRUKTUR KEPEMILIKAN, STRUKTUR PENGELOLAAN TERHADAP NILAI PERUSAHAAN: KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Almikyala, Almikyala; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test the influence ownership structure and management structure to the firm valuewith the financial performance as the intervening variable. The population of this research is all companieswhich are listed in Indonesia Stock Exchange (IDX). The samplesproperty, real estate and building constructioncompanies which are listed in the IDX in 2011-2014 periods. The samples are 11 companies which have beenselected by purposive sampling. The analysis method has been carried out by using multiple regressions analysistechnique.Based on the result of analysis, it can be concluded that the ownership structure which is proxy bymanagerial ownership and institutional ownership, it is managerial ownership which give positive influence tothe financial performance and firm value and the result of ownership structure give influence to the firm valuethrough financial performance cannot be proven since the result of direct coefficient value is larger. Financialperformance (ROA) give positive influence to the firm value (PBV). Therefore, it can be concluded that thefinancial performance cannot mediate between the ownership structure and management structure to the firmvalue.Keywords: Ownership structure, management structure, financial performance, firm value.